Development of Dolly Technique Videos (In, Out, Sideways, Chasing, Establishing) and Analysis of Their Application in Cinematography Learning - Vivian Febri Ningsih; Jimmy Pratama; Deli Deli (MASI Mandiri Edukasi, 2026)
This study addresses the lack of structured, empirically tested learning media for dolly camera movement techniques in formal cinematography education, where students often understand theory but struggle to translate it into practical and emotionally expressive camera work. The research aims to develop an instructional video demonstrating five key dolly movements (Dolly In, Dolly Out, Dolly Sideways, Dolly Chasing, and Dolly Establishing) using the Multimedia Development Life Cycle (MDLC) framework and to evaluate its effectiveness in improving students’ conceptual understanding, functional application, emotional interpretation, and self-efficacy. A quasi-experimental one-group pretest–posttest design was applied to 100 purposively selected cinematography and multimedia students, using a 20-item Likert-scale questionnaire that had been validated (item–total correlations 0.38–0.78) and shown to be reliable (Cronbach’s Alpha 0.81). The instructional video (duration 2 minutes 5 seconds, distributed via YouTube) was designed according to cognitive load and multimedia learning principles, integrating visual demonstrations, narration, and on-screen cues within the MDLC stages of concept, design, material collection, assembly, testing, and distribution. Results show substantial learning gains, with mean scores increasing from 2.80 (pretest) to 3.89 (posttest), representing a 62.7% improvement across all measured competency domains, and both the paired sample t-test and Wilcoxon signed-rank test indicated statistically significant differences between pretest and posttest scores (p < 0.001), confirming that the MDLC-based instructional video significantly enhances students’ conceptual comprehension, practical readiness, and confidence in applying dolly camera movements.